2004
DOI: 10.1128/aac.48.9.3625-3629.2004
|View full text |Cite
|
Sign up to set email alerts
|

National Surveillance of Methicillin-Resistant Staphylococcus aureus in Belgian Hospitals Indicates Rapid Diversification of Epidemic Clones

Abstract: Methicillin-resistant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 22 publications
5
63
1
Order By: Relevance
“…Low-level-resistant MRSA strains were referred to the reference laboratory between 1995 and 2005 to confirm oxacillin resistance. They were all mecA positive and exhibited low-level MICs to oxacillin ranging from 0.5 to 16 mg/liter, with a median of 8 mg/liter, by the agar dilution method (4,5,7). Of the last strains, five mecA-positive isolates were phenotypically categorized as oxacillin susceptible by CLSI breakpoints, with oxacillin MICs of Յ2 mg/liter and were therefore defined as "cryptic MRSA strains."…”
Section: Methodsmentioning
confidence: 99%
“…Low-level-resistant MRSA strains were referred to the reference laboratory between 1995 and 2005 to confirm oxacillin resistance. They were all mecA positive and exhibited low-level MICs to oxacillin ranging from 0.5 to 16 mg/liter, with a median of 8 mg/liter, by the agar dilution method (4,5,7). Of the last strains, five mecA-positive isolates were phenotypically categorized as oxacillin susceptible by CLSI breakpoints, with oxacillin MICs of Յ2 mg/liter and were therefore defined as "cryptic MRSA strains."…”
Section: Methodsmentioning
confidence: 99%
“…Although SCCmec IV is associated with CA-MRSA (26,38), SCCmec IV is also distributed among HA-MRSA strains. For instance, SCCmec IV HA-MRSA was found in this study and found among HA-MRSA isolates from European countries and the United States with high frequency (3,6,8,33).…”
Section: Discussionmentioning
confidence: 92%
“…Interpretive criteria for use in comparing complex PFGE patterns in outbreaks have been applied to nonoutbreak situations to track the national and international dissemination of S. aureus clones (44). The use of PFGE typing with adjusted interpretation criteria for grouping patterns with Ͻ7 bands difference has been shown to correspond to clonal assignments made by other methods (12). The main criticisms of this technique for S. aureus are that PFGE may on occasion be too discriminatory for other than local or short-term epidemiological analyses, the arbitrary nature of the interpretive criteria used, and the occasional requirement for subjective analysis of complex band patterns (30).…”
mentioning
confidence: 99%
“…An automatically curated, Internet-accessible spa sequence database is now available (1). Several recent epidemiological studies have used PFGE and/or spa typing to determine the genetic relatedness of large numbers of isolates and MLST/SCCmec typing for further characterization of representative isolates of each genotype found (3,12,18).…”
mentioning
confidence: 99%